Evolution of soil carbon stocks under Miscanthus × giganteus and Miscanthus sinensis across contrasting environmental conditions. Issue 1 (24th October 2020) - Ouattara, Malick S.; Laurent, Anabelle; Ferchaud, Fabien; Berthou, Magali; Borujerdi, Elsa; Butier, Arnaud; Malvoisin, Pierre; Romelot, Dominique; Loyce, Chantal
Abstract: Miscanthus is a C4 bioenergy perennial crop characterized by its high potential yield. Our study aimed to compare the carbon storage capacities of Miscanthus sinensis ( M. sinensis ) with that of Miscanthus × giganteus ( M. × giganteus ) in field conditions in different types of soils in France. We set up a multi‐environment experimental network. On each trial, we tested two treatments: M. × giganteus established from rhizomes (Gr) and M. sinensis transplanted seedlings (Sp). We quantified the soil organic carbon (SOC) stock at equivalent soil mass for both genotypes in 2014 and 2019 and for two sampling depths: L1 (ca. 0–5 cm) and L1‐2 (ca. 0–30 cm). We also calculated the total and annual variation of the SOC stock and investigated factors that could explain the variation and the initial state of the SOC stock. ANOVAs were performed to compare the SOC stock, as well as the SOC stock variation rates across treatments and soil layers. Results showed that the soil bulk density did not vary significantly between 2014 and 2019 for both treatments (Gr and Sp). The SOC concentration (i.e. SOC expressed in g/kg) increased significantly between 2014 and 2019 in L1, whereas no significant evolution was found in L2 (ca. 5–30 cm). The SOC stock (i.e. SOC expressed in t/ha) increased significantly in the superficial layer L1 for M. × giganteus and M. sinensis, by 0.48 ± 0.41 and 0.54 ± 0.25 t ha −1 year −1 on average, respectively, although no significant change was detected in the layer L1‐2 for both genotypes. Moreover, SOC stocks in 2019 did not differ significantly between M. × giganteus and M. sinensis in the soil layers L1 and L1‐2. Lastly, our results showed that the initial SOC stock was significantly higher when miscanthus was grown after set‐aside than after annual crops. Abstract : Miscanthus is a C4 bioenergy perennial crop. Our study aimed to compare the carbon storage capacities of Miscanthus sinensis with that of Miscanthus × giganteus in field conditions in different types of soils in France. Results showed that the soil organic carbon (SOC) stock increased significantly in the superficial layer L1 (ca. 0–5 cm) for Miscanthus × giganteus and M. sinensis . Besides, no significant change on SOC stock was detected in the layer L1‐2 (ca. 0–30 cm) for both genotypes. Lastly, SOC storage did not differ significantly between Miscanthus × giganteus and M. sinensis in the soil layers L1 and L1‐2.